Impact Of Clinical Pharmacist-Led Interventions on Short Term Quality Of Life Among Multiple Sclerosis Patients Taking Disease-Modifying Therapy - Zahraa Abbas Munaf; Samer Imad Mohammed; Gheyath Abd Ali Shallal Al-Gawwam (Iraqi Journal of Pharmaceutical Sciences)
Multiple Sclerosis has a substantial impact on a patient's quality of life. Pharmacists have a significant effect on the treatment of people with multiple sclerosis (MS) and may contribute to enhancing their quality of life (QoL). This study aims to evaluate the efficacy of pharmacist-led intervention (PI) on the quality of life of Patients with multiple sclerosis taking disease-modifying therapy (DMTs). This was a Pre-Post intervention study on patients with relapsing-remitting multiple sclerosis and receiving DMTs who attended a neurological consultant clinic in the medical city of Baghdad. Each patient received two educational sessions: The first at baseline after filling the face validation Arabic version of multiple sclerosis quality of life (MSQOL-29item) at baseline and the second after a month. each session lasted approximately 30-45 minutes, and the patients received educational counselling. A formal Arabic pamphlet was prepared for each patient. Then, After two months, The researcher asked the patients to refill the same questionnaire. eighty patients with RRMS were enrolled in the study, and sixty-five of these patients ultimately completed the study. The mean age of participants is 30.64+_8.54. The clinical pharmacist's intervention significantly improved the physical health composite (PHC) and mental health composite(MHC). only physical function in the PHC and changes in health were non-significantly affected by pharmacist intervention. The changes in scores before and after intervention were non-significantly differences in all demographic data groups. Finally, the study concluded that the clinical pharmacist-led educational intervention may enhance the quality of life of multiple sclerosis patients and play a crucial role in reducing DMTs complications.